Theoretical Study on the Reactions of Pd+ and Pd with CO2 in Gas Phase - Dai, Guo-Liang; Yan, Zhen-Zhong; Wu, Jun-Yong; Wang, Chuan-Feng; Chen, Hao; Zhong, Ai-Guo (Asian Journal of Chemistry, 2011)
Density functional theory (DFT) calculations have been performed to explore the potential energy surfaces of C-O bond activation in CO2 molecule by gas-phase Pd+ cation and Pd atom, for better understanding the mechanism of second-row metal reacting with CO2. The minimum energy reaction path is found to involve the spin inversion in the different reaction steps. This potential energy curve-crossing dramatically affects reaction energetic. The present results show that the reaction mechanism is insertion-elimination mechanism along the C-O bond activation. All the theoretical results can lead us to understand deeply the mechanism of the reactions of Pd2+ and Pd with CO2 in gas phase and may be helpful for the further experimental investigation of the reaction.